Alpha-1 Antitrypsin Deficiency-Associated panniculitis: A survey of lived experience. - Jaiden Townsend; Reem Alluhibi; Nicky Lynch; Richard Woolf; Aileen Marshall; David A Lomas; John R Hurst (PLoS ONE, 2025)
Introduction Alpha-1 Antitrypsin Deficiency (AATD)-associated panniculitis is a rare inflammatory condition characterized by painful subcutaneous plaques or nodules, often accompanied by ulceration or oily discharge. Despite its clinical and emotional burden, limited data exist on the lived experiences of individuals with this condition. Method An international online survey was conducted between April and July 2024, targeting individuals with AATD-associated panniculitis. The survey, co-designed with an affected individual and multi-disciplinary specialists, included 32 questions on demographics, diagnostic journey, life impact, and treatments. Responses were analysed using descriptive statistics and thematic analysis. Results 41 responses were included in the analysis (68% female; mean age 52.3 years). Participants reported lesions at diverse sites, affecting the lower and upper limbs, followed by the trunk, buttocks, and genitalia. 41.5% experienced both ulceration and oily discharge. 61% of participants reported being misdiagnosed which negatively affected their mental health. More than half of respondents 'strongly agreed' or 'agreed' that living with alpha-1 panniculitis had made them anxious. Access to specialist care was a major concern, with 69% finding it difficult to obtain specialist advice. Treatments varied, and augmentation therapy was identified as the subjectively the most effective. Open-ended responses revealed gaps in healthcare professionals' awareness and highlighted the need for better mental health support and specialist access. Conclusion AATD-associated panniculitis significantly impacts physical, emotional, and social well-being. Addressing gaps in diagnosis and treatment, increasing healthcare providers awareness, and adopting multidisciplinary approaches are essential to improve individuals' outcomes and quality of life.